Sensitivity of rapid antigen tests for Omicron subvariants of SARS‐CoV‐2 - Sakai‐Tagawa, Yuko; Yamayoshi, Seiya; Halfmann, Peter J.; Wilson, Nancy; Bobholz, Max; Vuyk, William C.; Wei, Wanting; Ries, Hunter; O'Connor, David H.; Friedrich, Thomas C.; Sordillo, Emilia M.; Bakel, Harm; et al. (Journal of medical virology, 2023)
Diagnosis by rapid antigen tests (RATs) is useful for early initiation of antiviral treatment. Because RATs are easy to use, they can be adapted for self‐testing. Several kinds of RATs approved for such use by the Japanese regulatory authority are available from drug stores and websites. Most RATs for COVID‐19 are based on antibody detection of the SARS‐CoV‐2 N protein. Since Omicron and its subvariants have accumulated several amino acid substitutions in the N protein, such amino acid changes might affect the sensitivity of RATs. Here, we investigated the sensitivity of seven RATs available in Japan, six of which are approved for public use and one of which is approved for clinical use, for the detection of BA.5, BA.2.75, BF.7, XBB.1, and BQ.1.1, as well as the delta variant (B.1.627.2). All tested RATs detected the delta variant with a detection level between 7500 and 75 000 pfu per test, and all tested RATs showed similar sensitivity to the Omicron variant and its subvariants (BA.5, BA.2.75, BF.7, XBB.1, and BQ.1.1). Human saliva did not reduce the sensitivity of the RATs tested. Espline SARS‐CoV‐2 N showed the highest sensitivity followed by Inspecter KOWA SARS‐CoV‐2 and V Trust SARS‐CoV‐2 Ag. Since the RATs failed to detect low levels of infectious virus, individuals whose specimens contained less infectious virus than the detection limit would be considered negative. Therefore, it is important to note that RATs may miss individuals shedding low levels of infectious virus.